2015
DOI: 10.1093/jamia/ocv092
|View full text |Cite
|
Sign up to set email alerts
|

Extracting relations from traditional Chinese medicine literature via heterogeneous entity networks

Abstract: This study exploits the power of collective inference and proposes an HFGM based on heterogeneous entity networks, which significantly improved our ability to extract relations from TCM literature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 37 publications
0
24
0
Order By: Relevance
“…They are a rich bio-resource for drugs of traditional medicinal systems, modern medicines, nutraceuticals, food supplements, folk medicines, pharmaceuticals, intermediates, and chemicals for synthetic drugs (Hammer et al, 1999 ). Medicinal uses are well-described in the Indian Ayurveda (Patwardhan, 2005 ), in Traditional Chinese Medicine (Wan et al, 2016 ), and in various European historical documents (Ginsburg and Deharo, 2011 ). However, indigenous knowledge in a particular region is an important component of traditional medicine, which is widely practiced by the tribal communities throughout India.…”
Section: Discussionmentioning
confidence: 99%
“…They are a rich bio-resource for drugs of traditional medicinal systems, modern medicines, nutraceuticals, food supplements, folk medicines, pharmaceuticals, intermediates, and chemicals for synthetic drugs (Hammer et al, 1999 ). Medicinal uses are well-described in the Indian Ayurveda (Patwardhan, 2005 ), in Traditional Chinese Medicine (Wan et al, 2016 ), and in various European historical documents (Ginsburg and Deharo, 2011 ). However, indigenous knowledge in a particular region is an important component of traditional medicine, which is widely practiced by the tribal communities throughout India.…”
Section: Discussionmentioning
confidence: 99%
“…The data set of paired herbs was incorporated into the SHT topic modeling process. We conducted treatment pattern mining through LDA, LinkLDA and SHT model, and calculated perplexity on different number of topics, which vary from 10 to 100. Table 2 shows the probability distributions of 5 discovered topics in SHT model.…”
Section: Overall Performance and Discussionmentioning
confidence: 99%
“…This tripartite information network derived more accurate information than linking symptom and herb alone. Wan et al [10] used a heterogeneous factor graph model (HFGM) to infer the multiple types of relations (e.g., herb-syndrome, herbdisease) from the entire corpus of TCM literature. Zhao et al [13] found that a novel machine learning algorithm, minimum reference set-based multiple instance learning, was superior to other machine learning algorithms for TCM syndrome differentiation.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, from Table 3 we can see, there are not many entities about "tongue body" (7), "tongue coating" (10), "pulse" (22) and "both tongue body and tongue coating" (2), while they have large quantity of annotations (3789, 4978, 6148, 793). Hence one can see that the expressions of "tongue body", "tongue coating", "pulse" and "both tongue body and tongue coating" are relatively consistent and frequently-used in TCM clinical records.…”
Section: Examples Of Special Entities and Analysismentioning
confidence: 99%